PREVALENCE AND FACTORS CONTRIBUTING TO DELAYED ACCESS TO EMERGENCY OBSTETRIC CARE AMONG MOTHERS IN EASTERN INDIA: A CROSS-SECTIONAL STUDY - Kumari, Priti; Kumari, Sheela; Kumari, Usha (Student's Journal of Health Research Africa, 2024)
Background Maternal mortality represents a significant public health challenge in underdeveloped countries, where numerous women succumb to pregnancy-related complications. Major contributing factors include delays in recognizing medical emergencies and accessing appropriate healthcare services. Analyzing these delays is essential for formulating effective strategies to enhance maternal health outcomes. This study seeks to examine the incidence rates as well as other variables that delay expecting mothers from seeking emergency care. Methods This cross-sectional study, conducted at Jawahar Lal Nehru Medical College & Hospital in Bhagalpur, Bihar, enrolled 120 women who sought maternity services. Data were collected using a validated questionnaire administered by trained interviewers. Statistical analysis included descriptive and multivariate logistic regression to identify factors associated with delays in seeking obstetric care. Results Of the 120 respondents, 86 provided consent and were interviewed, resulting in a response rate of 72%. The average delay in seeking obstetric treatment was approximately 1.5 hours, with 66.7% of participants reporting difficulty in deciding to seek care. Women aged 20-34 and those with lower educational levels experienced significantly higher delays in seeking treatment. Income, employment status, and antenatal care follow-up also influenced maternal delays. Conclusion The study highlights significant delays in seeking obstetric care among women, particularly in younger and less educated populations. Improving awareness and access to maternal healthcare services is essential to reduce these delays. Recommendations To enhance the maternity referral system, the hospital should work more closely with primary health care sub-facilities, like the liaison office. Road accessibility, quality, proximity, and modes of transit to medical institutions and the community would all be encouraged by the government. Finally, more research on the community-based study is required.